A WOMEN'S INHERITANCE RIGHTS AMID LEGAL PLURALISM IN INDONESIA: A COMPARATIVE ANALYSIS OF ISLAMIC, CUSTOMARY, AND POSITIVE LAW: Indonesian - Hasna Mardanus; Kurniati; Zulhas’ari Mustafa (UIN Palopo, 2026)
AbstractThis study examines the regulation and implementation of women’s inheritance rights in Indonesia within the framework of legal pluralism. As a country with a pluralistic legal system, Indonesia recognizes three inheritance law systems that coexist and develop within society, namely Islamic inheritance law, customary inheritance law, and civil inheritance law (Burgerlijk Wetboek/Civil Code), each of which has different characteristics in regulating the position of women as heirs. This research aims to analyze the regulation of women’s rights within these three legal systems, examine their implementation in social realities, and explore the impact of legal pluralism on the fulfillment and protection of women’s rights in the inheritance system. This research is a library research employing a normative legal approach. The data were obtained through document studies of primary and secondary legal materials, including legislation, the Qur’an, the Compilation of Islamic Law, the Civil Code, books, and relevant scientific journals. The collected data were then analyzed qualitatively using descriptive and comparative approaches. The findings indicate that both Islamic law and civil law fundamentally recognize and protect women’s rights as heirs, although they are based on different concepts of justice. Meanwhile, under customary law, the position of women is strongly influenced by the kinship system adopted by the community. In practice, the implementation of women’s inheritance rights still faces various obstacles, such as patriarchal culture, patrilineal kinship systems, and the low level of legal awareness within society. Legal pluralism also creates legal uncertainty and the potential for injustice due to differences in regulations among the existing legal systems. Therefore, legal harmonization and the strengthening of a gender justice perspective are necessary to ensure that the protection of women’s rights in the inheritance system can be realized more fairly and optimally. Keywords: Legal pluralism; women’s rights; inheritance